Potential predictive value of JAK2 expression for Pan-cancer response to PD-1 blockade immunotherapy - Peng, Jie; Xiao, Lu-Shan; Dong, Zhong-Yi; Li, Wen-Wen; Wang, Kun-Yuan; Wu, De-Hua; Liu, Li (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Recent clinical studies have shown promise for targeting programmed cell death protein-1 (PD-1) and programmed cell death ligand 1 (PD-L1) signaling in malignant tumors. However, reliable biomarkers for predicting who would benefit from anti-PD-1/PD-L1 inhibitors have not been fully elucidated. Methods: Here, patients from The Cancer Genome Atlas Pan-Cancer database (N=9,315) were classified into three groups based on the tri-sectional quantiles of their Janus kinase 2 (JAK2) RNA expression levels. Sample mRNA expression of PD-L1 and mutational load, CD8A expression [representing CD8+ cytolytic T lymphocytes (CTLs)], cytolytic activity (“CYT”) expression, and viral association were compared among groups. Results: High mRNA expression and gene amplification of PD-L1 were both significantly associated with high JAK2 expression (P